The compilation of an educational package to improve the psychological status of kids of Shahed and veterans’ families and compare its efficacy with cognitive processing therapy on distress tolerance and cognitive regulation of their emotions - Namjoo, Farhad; Sajjadian, Ilnaz; Golparvar, Mohsen (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed at compiling an educational package to improve the psychological status of kids of families of shahed and veterans and compare its efficacy with cognitive processing therapy on distress tolerance and cognitive regulation of their emotions. Method: The research method was a combinative type of exploratory-sequential approach design and contained two qualitative and quantitative dimensions. The qualitative part aimed to determine the content, structure, and final form of the educational package to enhance the psychological status of the kids of families of shahed and veterans based on their life experiences. The qualitative approach has been used to compile an educational package to improve the psychological status of the kids of shahed and veterans, and the quantitative approach has been used to compare its efficacy with cognitive processing therapy. And a quasi-experimental method with a pre-test-post-test design and a control group and two months of follow-up was used in this study. In addition to scientific texts, the statistical population of the qualitative part of the research included all the kids of families of shahed and veterans of Yasuj city that were studying in Shahid high schools and Yasuj University during the academic year 2018-2019. The statistical population of the quantitative part consisted of all the kids of the shahed and veterans’ families of Yasuj city. The sampling of the qualitative part was conducted purposefully, and 15 people were interviewed with a semi-structured interview to achieve theoretical saturation. In the quantitative part, the purposive sampling method was used to select 45 kids of shahed and veterans’ families of Yasuj city, and they were randomly assigned to three groups of the first experimental group (15 people), the second experimental group (15 people), and control group (15 people). The first experimental group received a researcher-made educational package to improve the psychological state at eight weeks, and the second experimental group was treated with the cognitive processing therapy of Resick et al. (2007) in twelve weeks of 90 minutes. The research instruments included the Cognitive Emotion Regulation Questionnaire of Garnefski et al. (2002) and the Distress Tolerance Scale of Simons & Gaher (2005). The qualitative data were analyzed by the Phenomenology method and the approach highlighted by Colaizzi, and quantitative data were analyzed by repeated-measures analysis of variance and Tukey post hoc test. Results: The content of the package to improve the psychological status of the kids of families of shahed and veterans includes four main concepts: training to cope with grief and loss, coping and overcoming suffering, expanding social support, purposeful adaptation to circumstances, and situations. Also, the validity of the educational package was reported at 0.87. The results of the quantitative part indicated that the two groups of the educational package to improve the psychological status of kids of the shahed and veterans and cognitive processing therapy were effective on cognitive emotion regulation (F = 3.64, P = 0.035), and distress tolerance (F = 8.70, P = 0.001), and this effect was constant in the follow-up stage. Furthermore, according to the results of the Tukey post hoc test, there was no significant difference between the two experimental groups (P < 0.05). Conclusion: as the educational package of improving the psychological status and the treatment of cognitive processing promote distress tolerance and cognitive regulation of emotion, therefore it is concluded that they can be used to improve distress tolerance and cognitive emotion regulation among kids of the shahed and veterans’ families.